Quality of Location in Regions and Economic Efficiency of Private Companies in Poland - Wierzbicka, Wioletta (Olsztyn Economic Journal, 2013)
Evaluation of the correlation between the economic efficiency level of private companies in Poland and the quality of location in the regions was the aim of the study. Based on the conducted analyses it was established that the level of sales markets absorptiveness shows the strongest correlation with the level of economic efficiency of the companies surveyed. The majority of regions characterised by absorptive sales markets also recorded good results in economic efficiency of companies located there while voivodships with low internal demand were characterised by definitely lower efficiency. Increasingly strong correlation was also recorded between the economic efficiency level of the companies surveyed and the level of knowledge in the regions. This may be the signal that currently the location factors of "soft" nature present increasing influence on the efficiency of companies and it is not impossible that their importance will continue increasing.